2019
DOI: 10.1121/1.5134781
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and selective production of syllable duration and fundamental frequency as word segmentation cues by French-English bilinguals

Abstract: The effects of musicality and language background on cue integration in pitch perception

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Nineteen participants had a relative language dominance index below 1, suggesting that they were more proficient in French than in English, regardless of their L1, and one participant obtained a relative language dominance index of 1, indicating that they performed equally well in both versions of the task (Birdsong, 2015; Treffers‐Daller & Korybski, 2015). Although verbal fluency tasks are generally used to probe vocabulary size and not participants' speech processing abilities, previous papers reported that relative language dominance scores based on verbal fluency tasks can predict bilingual participants' processing of specific prosodic cues (Gilbert et al, 2021) as well as their use of the same cues in production (Gilbert et al, 2019). Table 1 summarizes age of acquisition and language proficiency measures for the 42 participants included in the analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nineteen participants had a relative language dominance index below 1, suggesting that they were more proficient in French than in English, regardless of their L1, and one participant obtained a relative language dominance index of 1, indicating that they performed equally well in both versions of the task (Birdsong, 2015; Treffers‐Daller & Korybski, 2015). Although verbal fluency tasks are generally used to probe vocabulary size and not participants' speech processing abilities, previous papers reported that relative language dominance scores based on verbal fluency tasks can predict bilingual participants' processing of specific prosodic cues (Gilbert et al, 2021) as well as their use of the same cues in production (Gilbert et al, 2019). Table 1 summarizes age of acquisition and language proficiency measures for the 42 participants included in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the present study allows us to disentangle language‐specific effects (English vs. French) from effects related to order of acquisition (first vs. second language) and proficiency. This approach also allows the observation of potential directional effects as observed in previous research, where going from English‐L1 to French‐L2 might present different challenges compared to going from French‐L1 to English‐L2 (Gilbert et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Auditory stimuli consisted of recordings of the sentence pairs used in Gilbert et al (2019). These sentences involve twosyllable strings that represent either one bisyllabic word or two monosyllabic words (e.g., in English, [kiwi] can be interpreted as "kiwi" or "key we"; in French, [O R lOZ] can be interpreted as "horloge" -Eng.…”
Section: Sentence Contentmentioning
confidence: 99%
“…The selected recordings were also manually annotated by a trained bilingual coder in Praat (Boersma, 2001) following the method used in Gilbert et al (2019). Acoustic information about each syllable of interest was extracted using custom scripts developed onsite.…”
Section: Stimuli Recording and Acoustic Characteristicsmentioning
confidence: 99%